Orbital Response Indicates Nasal Pungency: Analysis of Biomechanical Strain on the Skin - Jalowayski, A. A.; Johnson, B. N.; Wise, P. M.; Schmid-Schonbein, G. W.; Cain, W. S. (Chemical senses, 2001)
Stimulation of the human nasal passage with pungent vapor elicits motor responses in a zone around the eye. This investigation addressed whether quantification of such responses, particularly activity of the orbicularis oculi muscle, could yield a sensitive index of nasal pungency. We placed an array of small, high-contrast targets just beneath the lower eyelid and videotaped their movement to capture deformation of the skin atop the orbicularis oculi during 3 s stimulation with pungent concentrations of ethyl acetate. Eleven subjects participated. Analysis of the movements served to determine mechanical strain, which yielded a single index that we termed 'maximum strain'. This increased with concentration of the vapor and with time during and just after stimulation. Comparison with psychophysical data showed that the strain became evident at concentrations just detectable as pungent. Maximum strain measured on the skin shows promise as an objective index of pungency.